Adhesion and Self-Healing between Monolayer Molybdenum Disulfide and Silicon Oxide. Issue 1 (December 2017) - Na, Seung Ryul; Kim, Youngchan; Lee, Changgu; Liechti, Kenneth; Suk, Ji Won
Abstract The adhesion interactions of two-dimensional (2D) materials are of importance in developing flexible electronic devices due to relatively large surface forces. Here, we investigated the adhesion properties of large-area monolayer MoS2 grown on silicon oxide by using chemical vapor deposition. Fracture mechanics concepts using double cantilever beam configuration were used to characterize the adhesion interaction between MoS2 and silicon oxide. While the interface between MoS2 and silicon oxide was fractured under displacement control, force-displacement response was recorded. The separation energy, adhesion strength and range of the interactions between MoS2 and silicon oxide were characterized by analytical and numerical analyses. In addition to the fundamental adhesion properties of MoS2, we found that MoS2 monolayers on silicon oxide had self-healing properties, meaning that when the separated MoS2 and silicon oxide were brought into contact, the interface healed. The self-healing property of MoS2 is potentially applicable to the development of new composites or devices using 2D materials.